Użyteczność edukacyjnej analizy transakcyjnej w kształtowaniu kultury pedagogicznej rodziców - Bereźnicka, Małgorzata (Edukacyjna Analiza Transakcyjna, 2016)
Transactional Analysis (TA) in some countries has been used at all levels of education, even the one concerning adults. In Poland this concept is still not very popular, so it should be more widely discussed. The paper presents the relationship between Transactional Analysis and educa- tion/upbringing, as well as the need for raising pedagogical culture among Polish parents (which isone of the conclusions of the author’s study). Raising children in today’s world cannot be solelybased on intuition and practical experience, but it should be based on high pedagogical culture. The possibility of practical applications of educational TA in this area would be beneficial for teachers, parents and children.